Deconstructing Textual Reality: rhizomatic writing as a disposition of Postmodern literary reflection - Bohovyk, Oksana; Bezrukov, Andrii; Haidar, Veronika (Respectus Philologicus, 2025)
The article draws on a Deleuzoguattarian view of the rhizome to examine literary connections within postmodern novels as multiple, non-linear, and non-hierarchical structures. Two symptomatic texts – Alexandar Hemonʼs The Lazarus Project (2008) and Markus Zusak’s Bridge of Clay (2018) – have been explored through a rhizomatic reading to illustrate how these novels embody the principles of the rhizome as a disposition of postmodern thinking. The stories demonstrate a distinctive form of rhizomatic writing characterised by fragmentation, the imitation of chaotic composition, the blending of various genre elements, and the inclusion of different types of art (intermediality). Moreover, the article focuses on the rhizomatic transformations of time that shape the literary landscape within the novels, addressing concepts of the pre-past, past, present, and future via the past. A rhizomatic way of creating fiction texts actualises the idea of interdisciplinarity as the topical project in the humanities. By employing the concept of the rhizome, the article engages with the deconstructive potential of postmodern literature and the dispositional mode of its representation.
Keywords: Deleuzoguattarian philosophy; Fictional reality; Literary connection; Postmodern thinking; Rhizomorphic reading